Effect of lateral fluorination in antiferroelectric and ferroelectric mesophases: synchrotron X-ray diffraction, dielectric spectroscopy and electro-optic study. (January 2016) - Dey, Kartick Ch.; Mandal, Pradip Kr.; Dabrowski, Roman
Abstract: Effect of lateral fluorination in the rigid core on several macroscopic and microscopic properties of a terphenyl based mesogenic chiral ester has been studied by synchrotron X-ray, dielectric and electro-optic techniques. Correlation lengths across the smectic planes, in para-, ferro- and antiferroelectric phases, are found to be significantly less in the fluorinated compound. Para to ferroelectric transition is found to be tricritical in nature in both the compounds. Fluorination resulted in slower response under a square pulse. Collective mode relaxation behaviour, with and without bias field, in all the phases are also found to be different in the fluorinated compound. Highlights: Fluorination changes transition temperatures considerably. Fluorination significantly decreases molecular correlation across smectic planes. SmA*–SmC* transition is nearly tricritical in both the systems. Fluorination resulted in slower response. Fluorination changes molecular dynamics substantially.